Heat Shock Proteins and Stress (Heat Shock Proteins,, 2018)
The book Heat Shock Proteins and Stress provides the most comprehensive review on contemporary knowledge on the role of HSP in Stress. Using an integrative approach to understanding the regulation of HSP responses, the contributors provide a synopsis of novel mechanisms by which HSP responses are regulated under normal physiological and pathophysiological conditions. Key basic and clinical research laboratories from major universities and academic medical hospitals around the world contribute chapters that review present research activity and importantly project the field into the future. The book is a must read for researchers, postdoctoral fellows and graduate students in the fields of Translational Medicine, Clinical Psychologists, Human Physiology, Zoologists, Botanists, Biotechnology, Molecular Medicine, Infectious Diseases Experts and Pathologists.